Validation of the phase difference method for atmospheric correction in GB-SAR. Issue 3 (2nd September 2022) - Liu, Jie; Yang, Honglei; Cai, Jianwei; Zhao, Binbin; Peng, Junhuan; Gao, Zhouzheng; Yang, Wenfu
ABSTRACT: The phase difference method can compensate the atmospheric disturbance in GB-SAR interferometry without the process of phase unwrapping, but its accuracy and effectiveness have not been analysed. This paper, therefore, analyses and validates this method by a simulation experiment and two real data experiments. Furthermore, we establish a quadratic model of the phase difference method to deal with the large range observation. The results show that the phase difference method can avoid possible phase unwrapping error and achieve a compensation accuracy (<0.3 mm) that is consistent with that of the traditional method.